The Influence of Service Quality and Security on Customer Satisfaction at PT. Bank Rakyat Indonesia Persero Tbk Kabanjahe Branch - Fauzia Mei Salsabillah; Amin Hou; Ahmad Fadli; Nasib Nasib; Ahmad Rivai (Proceeding of The International Conference on Economics and Business, 2022)
The demands and needs of the community for banking product services are increasing, however, in a situation of banking competition, banks need to work hard to get prospective customers and retain them, efforts to get customers are largely determined by the company's ability to provide quality services. One way to create quality service is that banks can differentiate themselves by consistently delivering higher quality than their competitors, the bank interacts with customers accompanied by control feedback and measures of success. The research method used in this study uses the Multiple Regression analysis method. with a total sample of 75 with results showing Based on the results of data analysis shows that service quality and security have a significant effect on customer satisfaction PT. Bank Rakyat Indonesia Persero Tbk Kabanjahe Branch